DNA Methylation Mechanism - Budak, Metin; Yıldız, Mustafa (Biochemistry, 2020)
'Simplicity is the ultimate sophistication'- Leonardo Da Vinci The methylation that occurs simply by attaching one or more methyl molecules to a DNA molecule continues to confuse the scientific world by creating highly complex molecular arrangements. Research on methylation mechanisms have discovered that this simple biochemical event (which adapts to the changing micro/macro environment of the organism, to diseases and even cancerous processes) has shown that it is actually not as simple as it seems. In the last 50 years, our efforts to understand these mechanisms and use them to benefit human beings have continued. With this book called "DNA methylation mechanism", in which we try to explain the effects on every stage of life, we hope that we have been able to create a resource book for everyone interested in this field, from students who are interested, to amateurs and professionals.